N235 Recovers Vanadium from Waste Solution of Vanadium Precipitation by Spent Catalyst - Jun ZHU; Mei GUO; Xinhai LIU; Yitong XU; Xiaopeng LI; Danyang LIU (Kuangchan zonghe liyong, 2024)
This is an article in the field of metallurgical engineering. For the vanadium precipitation waste liquid of a waste catalyst in a zinc smelter in Shaanxi, the vanadium in the vanadium precipitation waste liquid was recovered by solvent extraction method. The effects of N235 volume fraction, extraction ratio, extraction time and extraction stage on the vanadium extraction rate were investigated. The results showed that the extraction system with 30%N235+5%TBP+65% sulfonated kerosene was used for four-stage countercurrent extraction, the extraction ratio of VO/VA= 2∶1, the extraction time was t=5 min, and the extraction rate of vanadium was 95.68%. The volume fraction of Na2CO3 was 5%, the extraction ratio of V'o/V'A =4∶1, the extraction time was t=4 min, and the extraction rate of vanadium was 98.25% after three-stage counter-current extraction.